Vulvodynia: The Role of Inflammation in the Etiology of Localized Provoked Pain of the Vulvar Vestibule (Vestibulodynia) - Akopians, Alin L.; Rapkin, Andrea J. (Seminars in Reproductive Medicine, 2015)
Vulvar pain affecting the vestibule (vestibulodynia) is an enigmatic pain disorder that greatly affects quality of life and sexual functioning. The most common form of the disorder (localized provoked vulvodynia) is initiated by genital contact but is otherwise asymptomatic. Findings on examination are limited to excessive tenderness of the vestibule with light touch with cotton swab but may also include localized erythema and pelvic floor muscle tightness and tenderness. This review will summarize the literature regarding the role of inflammation in the genesis of the disorder. Some evidence exists for altered histology consisting of increased numbers of mast cells and nerve endings. Immunological abnormalities that have been reported include altered cytokines and neurokines. Abnormal inflammatory response and heightened sensitivity of the vaginal opening has been documented in a murine model of vaginal infection with Candida albicans. In vitro studies of fibroblasts from the vestibule of affected women with vestibulodynia demonstrate a proinflammatory response to C albicans that may be important in the initiation of pain. However, thus far none of the findings have led to adequate treatments.
Keywords: vulvodynia; localized provoked vulvodynia; vestibulodynia; inflammation